SISTEM INFORMASI BERBASIS WEBSITE UNTUK MENDORONG PEMBELAJARAN AKTIF DALAM PENGELOLAAN KEGIATAN MAHASISWA FKIP - Buwono, Sri; Firmansyah, Andang; Yansa, Hemri; Saptahadi, Dwija; Subarjo, Subarjo; Chorina, Malisa (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
This research aims to optima design as FKIP UNTAN digital ecosystem among students of the Faculty of Education and Teacher Training (FKIP) at Tanjungpura University (UNTAN) regarding academic articles and journals. Literacy in scientific literature is a crucial component in the development of students' competencies in the fields of education and educational sciences. FKIP as an educational institution needs to pay attention to the use of information technology in providing quality education for its students. Requires a Digital Ecosystem in the form of a system to manage information about accreditation, curriculum, class schedules and student activities. By using this Digital Ecosystem, information can be accessed and managed easily by authorized parties. This research only discusses Silangkau, which is a student activity management application from a Digital Campus ecosystem which will be named OPTIMA. The advantage is that apart from the base system from which the Digital Ecosystem design has been created, it will also help FKIP in producing the data needed to prepare for Faculty accreditation activities more easily and quickly. The nature of data management is in the form of student academic and non-academic data specifications.